2011
DOI: 10.1039/c1cp21335k
|View full text |Cite
|
Sign up to set email alerts
|

Structural modification of nanocrystalline ceria by ion beams

Abstract: Exceptional size-dependent electronic-ionic conductivity of nanostructured ceria can significantly alter materials properties in chemical, physical, electronic and optical applications. Using energetic ions, we have demonstrated effective modification of interface volume and grain size in nanocrystalline ceria from a few nm up to ∼25 nm, which is the critical region for controlling size-dependent material property. The grain size increases and follows an exponential law as a function of ion fluence that increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 35 publications
0
60
0
Order By: Relevance
“…The parameters used for the simulations were a sample density of $6.3 g cm À3 , with threshold displacement energies of 27 and 56 eV for the O and Ce atoms respectively [19,20]. This gave an average fluence-to-dpa conversion factor of 0.54 dpa per 10 14 ions cm À2 [21]. Post-irradiation characterization was performed using the complementary techniques of Rutherford backscattering spectroscopy (RBS), transmission electron microscopy (TEM) and glancing incidence X-ray diffraction (GIXRD).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The parameters used for the simulations were a sample density of $6.3 g cm À3 , with threshold displacement energies of 27 and 56 eV for the O and Ce atoms respectively [19,20]. This gave an average fluence-to-dpa conversion factor of 0.54 dpa per 10 14 ions cm À2 [21]. Post-irradiation characterization was performed using the complementary techniques of Rutherford backscattering spectroscopy (RBS), transmission electron microscopy (TEM) and glancing incidence X-ray diffraction (GIXRD).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…7, where it can easily be seen that the grains undergo a rapid growth at low dpa levels before beginning to stabilize somewhat at higher dpa levels. Indeed, increasing the dose further (to a value of 108 dpa) results in additional growth of the grain size to an asymptotic value of $25 nm [21]. Previous work has shown that grain growth of nanocrystalline metallic systems under irradiation [25] follows the equation D n À D n 0 ¼ kUt, where n = 3, D is the grain size for a given dose, D 0 is the initial grain size, K is a constant and Ut is the ion dose.…”
Section: Grain Growth and Grain Boundary Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synergistic effects 28 56 (E < 0.5 MeV), the transfer of energy to atomic nuclei (nuclear 57 energy loss) dominates, leading to the displacement of atoms via 58 elastic scattering collisions between atomic nuclei in ballistic colli- 59 sion cascades. For high energy ions exceeding $1 MeV per nucleon 60 (MeV/u), particularly for swift heavy ions (E > 50 MeV), electronic 61 energy loss dominates, leading to intense local ionization that 62 can cause damage production [6], track formation [7] or damage 63 recovery [8], and the formation of long, straight ion tracks with 64 nanometer diameters by swift heavy ions has been exploited in a 65 range of nanoscience applications [9,10].…”
mentioning
confidence: 99%